A comparative evaluation of bilateral hippocampus and amygdala volumes with ADC values in pediatric primary idiopathic partial epilepsy patients - Taşkent, İsmail and Danışan, Gürkan and Yıldırım, Hanefi (Journal of Surgery and Medicine, 2019)
Aim: Approximately 70% of temporal seizures are hippocampal seizures, which are often concomitant with amygdala seizures. Seizures occurring in this region are usually complex partial. The aim of this study was to determine whether there was a significant change in hippocampus and amygdala volumes in idiopathic partial epilepsy patients without pathology on routine cranial MRI and to compare the hippocampus and amygdala ADC values with the control group. Methods: In this case-control study, 27 patients aged between 1-18 years, who were admitted to our hospital between the years of 2014 and 2017 and diagnosed with idiopathic partial epilepsy based on EEG and clinical findings were compared with 20 children in the control group, which consisted of twenty children of similar ages who were referred to our hospital with nonspecific complaints such as headache and dizziness and who underwent cranial MRI. Children with histories of any congenital diseases, acquired neurodegenerative diseases, intracranial infections, intracranial masses, and those who were perinatally affected were not included in the study. Drawings, volumetric measurements, and ADC calculations were performed by two separate evaluators (one neuroradiology and one radiology research assistant). Results: Hippocampus and amygdala volumes of the study group were decreased compared to the control group, but the results were significant only for the left hippocampus. Although ADC values of the study group were increased, the findings were statistically significant only for the left amygdala. Conclusion: In our study, we found that the hippocampus and amygdala volumes of patients diagnosed with idiopathic partial epilepsy were decreased ipsilateral to the seizure focus, and the ADC values of the ipsilateral amygdala were increased.